The Implementation of Peer Correction in Writing Instruction as an Effort to Support Deep Learning Policy - Rahmi Atiningrum; Rahmat Mulyono; Saryanto (Universitas Pakuan, 2026)
This study aims to improve writing skills through the implementation of peer correction techniques as an effort to support deep learning policy. The form of this study is Classroom Action Research (CAR). The subjects of the study were students of Class VIIC at SMP Negeri 2 Pengasih. The implementation of the study began with an initial survey in the form of score results and observations of writing instruction during Semester 1, followed by Cycle I and Cycle II, each consisting of four stages, namely planning, implementation, observation, as well as analysis and reflection. The data collection technique was conducted by examining the results of students’ writing abilities through students’ summative assessment results using a writing assessment rubric. The findings of this study indicate that the peer correction technique can improve the writing skills of Class VIIC students at SMP Negeri 2 Pengasih. The improvement in students’ writing skills can be observed from the results of students’ writing practice assessments. This is indicated by the average score of students’ text-writing skill assessments, which increased in each cycle. The average student score in Cycle I reached 69.97, while in Cycle II it reached 76.50. In addition, the number of students who achieved a good category in Cycle I was 20 students (62.5%), and in Cycle II increased to 27 students (84.38%). Furthermore, in Cycle II, there were 2 students (6.25%) who achieved a very good category..